White pomegranate (Punica granatum) peels extract bactericidal potency on Enterococcus faecalis - Eric Priyo Prasetyo; Widya Saraswati; Dian Agustin Wahjuningrum; Latief Mooduto; Rizka Firdaus Rosidin; Evelyn Tjendronegoro (Conservative Dentistry Journal, 2021)
Background: Enterococcus faecalis (E. faecalis) is the most resistant bacteria in the root canals and one of the causes of recurrent endodontic treatment. Enterococcus faecalis was not the only bacteria found in failed endodontic treatment but these bacteria can thrive in unfavorable environment. White pomegranate (Punica granatum) is known for its flavonoids and tannins that function as antimicrobial agent. White pomegranate extract is potential for use as disinfection or irrigation material. Purpose: This aim of this study was to determine the bactericidal potency of white pomegranate (Punica granatum) extract on E. faecalis growth. Methods: This study was an in vitro experimental observation. E. faecalis was obtained from stock culture taken from the root canal of recurrent endodontic treatment. E. faecalis from the serial dilution were cultured in blood agar media. Antibacterial potency was determined by colony calculation of E. faecalis growth in blood agar in colony forming unit (CFU) and conducted in 6 replications for each concentration group. Statistical analysis was done using one-way analysis of variance at 5% significance level. Results: White pomegranate peels extract concentrations of 3.125%, 6.25%, 12.5% and 25% provide significant decrease in the number of E. faecalis colony compared to the control group (p<0.05). No bacterial growth was found on 25%, 50% and 100% concentration. Conclusion: The potent minimal bactericidal concentration of white pomegranate peels extract on E. faecalis was 25%.